math

posted by .

rewrite the equation so that y is a function of x.then use the result to find y when x= -2,-1,0,1

-6x-1=-4y+2

  • math -

    Subtract 2 from both sides, then divide both sides by
    -4. Use the resulting equation to find y for the various values of x.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    rewrite each equation as afunction of x.-3y+4y=11 Where are the equations?
  2. Math

    How would you rewrite the equation y = 3x+1 as a function of x. Hmmm. It is written now as a function of x. Do you mean like this, where x is a function of y?
  3. algebra 116

    Rewrite the equation y = 5x – 2 as a function of x. This problem is already a function of x. y = 5x - 2 as a function of x. Rewrite the equation –x – 4y = 20 as a function of x. Graph f(x) = –3x – 2. Solve the system by graphing.
  4. math

    Rewrite the equation so that y is a function of x: 1. 2/3y+4=2x 2. 1/2(y+5)+4x=3x 3. Use the result in Ex. 1 to find y when x= -1, 0, and 2. 4. Use the result in Ex. 2 to find y when x= -1, 0, and 2. Thank you very much for any help.
  5. math

    Rewrite the equation so that y is a function of x: 1. 1/2(y+5)+4x=3x 2. Use the result in Ex. 1 to find y when x= -1, 0, and 2 __________ Can you please check if this is right?
  6. Math

    The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just don't …
  7. Math

    The graph of a quadratic function has vertex(3,-4) and passes through the point (4,1). Find the equation of the function in standard form. Rewrite the equation in general form. Could someone explain to me how to do this, just don't …
  8. Algebra

    Please help me with this algebra question?
  9. math

    rewrite the equation so that y is a function of x.then use the result to find y when x= -2,-1,0,1 6x-2y=10
  10. math

    rewrite the equation so that y is a function of x.then use the result to find y when x= -2,-1,0,1 -2y-3x-16=0

More Similar Questions